Síntese verde de sistemas do tipo volframita (CoWO4): uma investigação estrutural, magnética, eletroquímica, óptica, vibracional e energética - Azevêdo, Heytor Vitor Souza Bezerra de (2022)
In this work, an experimental study of cobalt tungstate (CoWO4) was developed, in which nanoparticles were produced by the Proteic Sol-Gel (SG) method. CoWO4 structure consists of six oxygen atoms surrounding each tungsten atom forming a wolframite-like monoclinic structure. This ternary oxide has potential application as materials used for battery-like charge storage, sensors, or particles for spectral optimization. The proteic sol-gel method was employed for the preparation of CoWO4 nanoparticles using two types of polymerizing agent: animal gelatin (collagen) and red algae agar-agar (Rhodophyta). This work is pioneering on the synthesis of wolframite (CoWO4) via a proteic sol-gel route that uses animal gelatin as polymerizing agent, as well as a new green route that uses red algae (Rhodophyta) agar-agar. Elementary and advanced characterization techniques were applied to provide a detailed understanding of the morphological, structural, optical, magnetic, and electrochemical properties of the produced CoWO4 nanoparticles, such as scanning electron microscopy, X-ray energy dispersive spectroscopy, thermal analysis, FTIR, Raman, UV-Vis-NIR spectroscopies, X-ray diffraction with Rietveld refinement, magnetization measurements, linear-cyclic voltammetry, and electrochemical impedance spectroscopy. CoWO4 nanoparticles present particle size distribution in the ranges of 36-68 nm and 31-85 nm for samples obtained with gelatin and agar-agar, respectively. Structural investigation by X-ray diffraction revealed a wolframite-type crystal structure with monoclinic Bravais network and P12/c1 point group. Based on Kubelka-Munk theory, the bandgap varied in the range of 2.5 to 0.74 eV. Raman spectroscopy demonstrated that the samples have 12 active phonons. The performance of CoWO4 as battery-like electrodes is attributed to a surface faradaic redox reaction mechanism related to the reversible valence state between Co2+ and Co3+. The discharge curves of CoWO4 fabricated by commercial gelatin and agar-agar indicated no substantial difference in electrochemical performance, with a maximum specific capacity of 77 C g-1 at a specific current of 1 A g-1. Magnetic evaluation at 300 K showed a paramagnetic behavior of the CoWO4 compound. In samples prepared with agar-agar, the magnetic moments ranged from 4.59 to 4.96 B (in Bohr magneton units), and in samples prepared with commercial gelatine, the magnetic moments ranged from 4.58 to 4.92 B. Fluorescence and plasmon band investigation revealed a structural relationship between amounts of defects and absorption of radiant energy, with the number of structural defects decreasing with increasing temperature. Furthermore, stoichiometric modification between the precursors allowed changes in photoluminescent and plasmonic properties, reaching maximum emission and absorption at 468 and 410 nm, respectively.